The association between leukoaraiosis and poor outcome in intracerebral hemorrhage is not mediated by hematoma growth - Sykora, Marek; Herweh, Christian; Steiner, Thorsten (Journal of stroke and cerebrovascular diseases, 2017)
Background: The significance of white matter lesions (WMLs) in intracerebral hemorrhage (ICH) remains unclear. We investigated the effects of WML on initial hematoma volume, hematoma growth, intraventricular extension, and clinical outcome in patients with spontaneous ICH. Methods: Computed tomography scans of 262 patients included in a placebo arm of a prospective, multicenter trial were used for a semi-quantitative analysis of white matter changes. A logistic regression analysis was used to explore the effects on hematoma volume, volume changes, intraventricular hemorrhage, and clinical outcome after 90 days. Results: The degree of WML was not associated with initial hematoma volume, absolute and relative hematoma growth, hematoma growth >33% or >6 mL, or with intraventricular extension. WML significantly increased the odds for poor outcome after 90 days (adjusted OR 1.4, 95% CI 1.1-1.8, P = .02). Conclusions: WMLs were not associated with initial hematoma volume, hematoma growth, or intraventricular extension. WMLs were associated with poor outcome independently.
Available online 23 February 2017
Gesehen am 21.06.2018